Augmented MIMO: Body-Mounted Antennas for Tiny Wearable Devices - Akihito Noda (Applied Sciences)
Multiple-input–multiple-output (MIMO), which uses multiple antennas at the transmitter and receiver, is now an essential technique for increasing communication capacity without widening the occupied radio bandwidth. However, antenna arrays within a deep subwavelength dimension degrade MIMO performance due to mutual coupling between the antenna elements. In particular, very small devices such as smartwatches encounter this problem. To address this, we propose Augmented MIMO, mounting a larger antenna array on the human body, for small wearable devices. The experimental results demonstrate throughput improvement with the proposed scheme, even if the overall antenna gain decreases with external body-mounted antennas. This work contributes to the future development of yet another scheme to improve the communication performance of small wearable devices—using the human body as a spacious antenna fixture.